Sequential and Parallel Tools for Model Checking Conditional Stable Properties in a Layered Way - Do, Canh Minh; Phyo, Yati; Ogata, Kazuhiro (IEEE access, 2022)
We invented a divide & conquer approach to conditional stable model checking so as to ease the state space explosion problem. As indicated by its name, the technique concentrates on conditional stable properties expressed as φ _{1} \leadsto \Box φ _{2} , where φ _{1} and φ _{2} are state propositions. The properties can be used to formalize desired properties that self-stabilizing systems should satisfy. Self-stabilization in distributed systems was first introduced by Dijkstra and became a very crucial concept in fault tolerance to design robust systems. However, designing self-stabilizing systems need much more effort than non-stabilizing ones because the former are subject to transient errors at any time. Therefore, it is worth dedicating to conditional stable properties. In this paper, we report a sequential tool and a parallel technique/tool for the divide & conquer approach to conditional stable model checking. Some experiments are also conducted showing that our sequential and parallel tools can ease the state space explosion and improve the running performance of model checking for conditional stable properties to a certain scope, respectively.